Amazonia, biodiversity, flying rivers and national security - Arce Rojas, Rodrigo Severo (2023)
This review and reflection article deals with the complex interrelationships between Amazonia, biodiversity, flying rivers and national security. The objective is to suggest that the Peruvian Armed Forces, taking into account their role in national security, proactively engage in the conservation of the Amazon, the fight to reverse biodiversity loss and mitigate the effects of climate change. There is a close interrelationship between biodiversity, biogeochemical cycles and hydrological cycles, so the conservation of the Amazon has a fundamental role to achieve the welfare objectives of the Peruvian population and even at a continental and global level. In this sense, the Armed Forces, through their spaces of higher studies, have the opportunity to contribute to debate and action with emphasis on genuine and deep sustainability.